"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought -- from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp -- than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view -- that is, to a radical approach to Polanyi's thought.
Keywords: Poor Law; WEBER, Max, 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Institutional Matrices Theory, or X- and Y-Theory: A Response to F. Gregory Hayden - Kirdina-Chandler, Svetlana (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article draws attention to issues about the institutional matrices theory (IMT) as perceived by and raised in the article by F. Gregory Hayden. To clarify the “controversial” points, I structure my response narrative along two lines. First, I present the prehistory of IMT, or X- and Y- theory, including earlier work by scientists related to the concept of institutional matrix. I connect the development of the actual IMT with the period of “perestroika” and the associated market experiments and reforms in Russia and Eastern European countries. One could see that the effects of market reforms in Russia were different in comparison with other countries in economic transition. I show that the institutional approach was accepted as more relevant to understanding the unexpected results in Russian society. I present IMT as a development of the ideas of Karl Polanyi and Douglas North to answer the challenges of explaining the real social and economic processes in Russia, as well as its wider application to a broader range of economic and social situations in different countries. Second, I then present the main IMT theses, giving special attention to the issues as perceived and raised by Hayden. In conclusion, I suggest the possibility of a joint project that combines IMT consideration and the social fabric matrix (SFM) concept of F. Gregory Hayden.
Keywords: HAYDEN, F. Gregory; Perestroika; Russia; economic policy; economics; institutional matrices theory; reciprocity

Food industry structure in Norway and Denmark since the 1990s: Path dependency and institutional trajectories in Nordic food markets - Klimek, Bjørn; Hansen, Henning Otte (Food Policy, 2017)
Structural changes in Norwegian and Danish food industry since the 1990s is analysed as a path dependent response to the neo-liberal turn. Norway entered the 1990s as a protected market and Denmark as case of an export oriented industry. These developmental strategies are rooted in early 20th century industrialisation and influenced by institutional transformations in the 1990s, such as EU and WTO. Mergers and acquisitions (M&A) are studied in the context of changing political environments. Explaining two different trajectories, we combine path dependency theories and a Polanyi inspired ‘varieties of capitalism’ framework with corporate strategy theories on food industry M&As. We identify two different types of path dependent development, a self-reinforcing in Denmark and a transformative ‘breaking point’ in Norway.
Keywords: Nordic food markets; World Trade Organization (WTO); agri-food chain; business planning; food economics; food industry - economic aspects; food industry structure; food marketing; food mergers and acquisitions (M&A); food policy; food supply management; institutional change; path dependency

Finance proud and industry vulnerable: When governments fail to defend the economic realm, citizens revolt - Pettifor, Ann (Juncture, 2017)
The subordination of society to self-regulating international markets is the reason why British workers and industries so often fall prey to predatory financiers, writes Ann Pettifor. It is also a fundamental cause of current political crises throughout the west – just as Karl Polanyi described almost 80 years ago.
Keywords: private equity firms; self-regulating market

Polanyi and Foucault on the Issue of Market in Classical Political Economy: Complementary Approaches to the Radical Theory of Social Control - Guizzo, Danielle; de Lima, Iara Vigo (Review of Radical Political Economics, 2017)
Studies have pointed out that the value of markets is related to their impact on the character of a society. Karl Polanyi's thesis about social disembeddedness attributed to 19th century economic liberalism the responsibility for consolidating the process of separating markets from society, which changed the dynamics between the state and population when economic rationality began dictating their connections. However, Polanyi only suggested analyses regarding power relations between these three elements and their effects on the social context. This paper argues that Michel Foucault's writings concerning technologies of power and biopolitics complement Polanyi's considerations insofar as they provide an understanding about how biopolitics emerged and how this led to a new posture of the state regarding population care and economic environment regulation.
Keywords: FOUCAULT, Michel, 1926-1984; biopolitics; classical economic liberalism; embeddedness; liberalism; political science; sociobiology; socioeconomic theory; socioeconomics

Karl Polanyi on economy and society: a critical analysis of core concepts - Hodgson, Geoffrey M. (Review of Social Economy, 2017)
The article presents the views of economic historian Karl Polanyi on the nature of economic and social embeddedness. Topics discussed include relationship between the economic and social embeddedness, the impact of the market economy, the transformation of society and production of material goods. Particular focus on limits of privatization, commodification, and marketization.
Keywords: business; capitalism; commodification; economic; economic activity; embeddedness; markets; social

Brexit and its Consequences - Pettifor, Ann (Globalizations, 2017)
In this brief essay, I argue that the ‘Brexit’ vote is but the latest manifestation of popular dissatisfaction with the utopian ideal of autonomous markets beyond the reach of regulatory democracy. Brexit represented the collective, if (to my mind) often misguided, efforts of those ‘left behind’ in Britain to protect themselves from the predatory nature of market fundamentalism. In a Polanyian sense, it is a form of social self-protection from self-regulating markets in money, trade and labour.
Keywords: BREXIT Referendum, 2016; Brexit; business; countermovement; democracy; double movement; financialization; markets; utopias

Financialization and Society's Protective Response: Reconsidering Karl Polanyi's Double Movement - Watkins, John P. (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Financialization challenges Karl Polanyi's thesis of double movement, the thesis that efforts to extend the market evoke efforts to protect humans, nature, and means of production from market forces. Financialization refers to the increased power of financial institutions. The government protects the incomes and assets of financial institutions, but it does little to protect the incomes and assets of households, which are necessary for people to afford healthcare, education, emergencies, retirement, and so on. Polanyi criticized nineteenthcentury civilization for transforming land, labor, and the means of production into commodities, using economic insecurity to motivate humans. The development of intangible property allowed business to expand the market in two ways: (i) restricting output to drive up profits and (ii) liquefying consumer assets to provide credit to consumers to increase spending. The implications of that process manifested themselves in the financial crisis of 2008. Market capitalism represented the attempt to organize commodities based on economic rationality. Similarly, the twentieth- and twenty-first-century capitalism represents the effort to "rationally" organize society according to the value of intangible assets. Both efforts failed, indicating the continued relevance of Polanyi's thesis.
Keywords: asset management; commons; double movement; financial services industry; financialization; global financial crisis, 2008-2009; intangible property; socioeconomic factors

An Evaluation of Institutional Matrices Theory Which Was Designed to Illustrate Differences Between Russian and Western Political Economies - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article is devoted to the evaluation of the institutional matrices theory (IMT), which was designed to illustrate the differences between Russian and Western political economic systems. IMT has no matrix, and it is an ideological declaration rather than a theory. It is a set of assertions and assumptions that are adopted without evidence, and then hypostatized to be Russian and Western socioeconomic systems. IMT literature claims to utilize the reciprocity, redistribution, and exchange model of Karl Polanyi (1944, 1957). However, IMT suffers from a number of assumptive and methodological problems in its application, the first of which consists of the complete exclusion of reciprocity from consideration. The first section of the article is an explanation of problems with IMT, and the second section demonstrates some particulars of the IMT problems with a real-world social fabric matrix from a Western nation.
Keywords: Russia; economic policy; economics; institutional economics; institutional matrices theory; social fabric matrix; socioeconomics